Studying the Texts of the Yakut Epic Olonkho: A Phenomenological Approach - Danilova, Vera Sofronovna; Kozhevnikov, Nikolay Nikolaevich (Journal of History Culture and Art Research, 2018)
The theoretical and methodological bases of the present research are based on the theory of Wolfgang Iser, which distinguishes between the concepts "text" and "literary work." "Text" is produced by the author and exists in a single variant, representing a symbolic code that is waiting for its implementation, before which it has only virtual meaning. "Literary work" is what arises in the act of reception - as a result of the reader's activity in the realization of the semantic potential of the text - and exists in a multitude of receptive variants. In the process of the reader's communication with the text, “the horizon of expectations" of the text, which contains the requirements for the reader coded in the text, interacts with “the horizon of expectations" of the reader, which is based on the requirements imposed on the text by the reader. The merging of the "horizons" is the key to an adequate understanding. In the present paper, the interaction of “the horizons of expectations" of the text and the reader is represented in the form of "windows", "created" by the text and the reader in the experience of the perceiving consciousness. "The expectations of the text" are considered in the form of "windows" formed by phenomena and horizons. They are attached to three levels of the structural features of the olonkho texts: the active (eventive) level, the level of accenting rhythms and the semiotic level, which are the most illustrative for the conducted research. "The expectations of the reader" are provided by three fundamental limits of dynamic equilibria (identification limit, communication limit and the limit of the rhythms of world harmony), which are attached to the levels of text singled out above.